GTP Hydrolysis by eRF3 Facilitates Stop Codon Decoding during Eukaryotic Translation Termination - Salas-Marco, Joe (American Society for Microbiology, 2004)
Translation termination in eukaryotes is mediated by two release factors, eRF1 and eRF3. eRF1 recognizes each of the three stop codons (UAG, UAA, and UGA) and facilitates release of the nascent polypeptide chain. eRF3 is a GTPase that stimulates the translation termination process by a poorly characterized mechanism. In this study, we examined the functional importance of GTP hydrolysis by eRF3 in Saccharomyces cerevisiae. We found that mutations that reduced the rate of GTP hydrolysis also reduced the efficiency of translation termination at some termination signals but not others. As much as a 17-fold decrease in the termination efficiency was observed at some tetranucleotide termination signals (characterized by the stop codon and the first following nucleotide), while no effect was observed at other termination signals. To determine whether this stop signal-dependent decrease in the efficiency of translation termination was due to a defect in either eRF1 or eRF3 recycling, we reduced the level of eRF1 or eRF3 in cells by expressing them individually from the CUP1 promoter. We found that the limitation of either factor resulted in a general decrease in the efficiency of translation termination rather than a decrease at a subset of termination signals as observed with the eRF3 GTPase mutants. We also found that overproduction of eRF1 was unable to increase the efficiency of translation termination at any termination signals. Together, these results suggest that the GTPase activity of eRF3 is required to couple the recognition of translation termination signals by eRF1 to efficient polypeptide chain release.